Soil Moisture Importance - Swaroop Meena, Ram; Datta, Rahul (IntechOpen, 2021)
Poor soil and water management are often related to insufficient or poor rainfall distribution around the world. In modern agriculture, over-cultivation, deforestation, overgrazing, and high dependence on an irrigated cropping system with water-intensive crops increase soil and water erosion. This book examines ways of improving soil moisture management to support environmental, food, social, and economic security under a sustainable ecosystem.